A Two‐Dimensional Metal–Organic Framework as a Fluorescent Probe for Ascorbic Acid Sensing. Issue 2 (18th January 2018) - Yue, Dan; Huang, Yike; Zhang, Jun; Zhang, Xin; Cui, Yuanjing; Yang, Yu; Qian, Guodong
Abstract : Ascorbic acid (AA) is an important biological molecule, but the detection of AA is still a huge challenge. Therefore, highly sensitive and selective fluorescent sensors for AA determination are urgently demanded. In this work, the new organic linker 4, 4′‐(1 H ‐pyrazole‐1, 3‐diyl)dibenzoic acid (H2 L) was prepared to construct the new two‐dimensional metal–organic framework (MOF) ZnL(H2 O) (ZJU‐137, ZJU = Zhejiang University). The ZJU‐137 MOF demonstrates high selectivity and sensitivity for the detection of AA through fluorescence quenching. The detection limit for AA was 34 nM, and a wide linear concentration‐dependent response (0–60 µm ) was observed; hence, ZJU‐137 has promising potential for the determination of AA in practical applications. Abstract : A 2D metal–organic framework (ZJU‐137) demonstrates good water stability and high selectivity and sensitivity for ascorbic acid determination through fluorescence quenching.